Exploring the Technology Orientation Influence on the Innovativeness-Performance Relationship of Manufacturing SMEs - Saqib, Muhammad; Zarine, Robin; Mohamed Udin, Zulkifli (Inderscience Publishers, 2018)
Globally, organisations have been facing excessive challenges due to the rapid changes within business environments. An empirical approach is used with smart PLS as the investigative tool to explore the impact of innovativeness within manufacturing SMEs on performances while using the technology as a moderating factor. Insignificant impact of innovativeness on performances of manufacturing SMEs in Oman could be observed. It is suggested that the way forward is to enhance capability for or support research and development, promote collaboration among SMEs, review government legislation and support towards the SMEs, have a well-focused capacity building plan, and strive for more competitive markets